Exact Sciences and the Problem of Integral Understanding of the Social Reality - Näpinen, Leo (Problemos, 2004)
It is argued whether the concepts and methods of exact sciences are completely unsuitable for integral understanding the social reality. These concepts and methods can only be used for modelling social processes, whereas the modelling can start only after the social phenomenon has been understood by the common sense, philosophy and historical research. Therefore the integral understanding of the social reality in all its complexity and diversity remains the task of social scientists themselves. What is needed is the co-operation between exact and historical sciences, and not the attempt to replace one by the other.
Keywords: exact sciences; historical sciences; social reality; self-organisation; autopoetic systems